An investigational study on properties of concrete produced with industrial waste red mud. (2021) - Chavan, S.P.; Salokhe, S.A.; Nadagauda, P.A.; Patil, S.T.; Mane, K.M.
Abstract: The requirements for leading a proficient life is challenging for the rapid development of industries and they partially fulfil their tasks since many factors are not overcome by them successfully and one of that is safe disposal and utilization of waste generating at the end. All countries produces an enormous amount of different types of waste materials as by products from different sectors like industrial, agricultural etc. These waste materials if not deposited safely it may be hazardous. Also it is seen that for manufacturing of cement required huge amount of energy, causes releasing of huge CO2 in atmosphere resulting formation of environmental problems. So it is very important to use of industrial waste in construction industry especially for replacement of the cement in some proportion. Intension of this study is to inspect the performance of concrete by substituting cement by red mud. In this work, cement was partly replaced by red mud (RM) in different percentages (0%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% and 20%), with 0.44 water cement (W.C) ratio with reference of Indian standard (IS) 10262:2019 guidelines, M30 grade concrete were prepared. Flow properties and strength properties like flexural, compressive, split tensile strength and chloride permeability tests were tested for 28 days on concrete with various mix proportions and test results were correlate with results of reference concrete. The study reveals that, partly replacing of 12% factory cement by red mud (RM) yields maximum strength, superior chloride permeability with better micro structure than conventional concrete.